2018
DOI: 10.4103/0366-6999.229889
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Daytime Sleepiness in Parkinson's Disease

Abstract: Objective:Excessive daytime sleepiness (EDS) is one of the most common sleep abnormalities in patients with Parkinson's disease (PD), yet its multifactorial etiology complicates its treatment. This review summarized recent studies on the epidemiology, etiology, clinical implications, associated features, and evaluation of EDS in PD. The efficacy of pharmacologic and non-pharmacologic treatments for EDS in PD was also reviewed.Data Sources:English language articles indexed in PubMed and Cochrane databases and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 82 publications
0
31
0
Order By: Relevance
“…Sleep disturbances are one of the most common and disabling nonmotor manifestations of Parkinson's disease (PD), affecting almost 80% of patients (Shen et al., 2018). Disrupted sleep–wake cycles contribute to poor quality of life and increased risk for accidents, leading to increased morbidity and mortality in the PD population (Rocha et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep disturbances are one of the most common and disabling nonmotor manifestations of Parkinson's disease (PD), affecting almost 80% of patients (Shen et al., 2018). Disrupted sleep–wake cycles contribute to poor quality of life and increased risk for accidents, leading to increased morbidity and mortality in the PD population (Rocha et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…EDS affects a large percentage of PD patients, and it is considered to be a possible preclinical marker of the disease itself (Abbott et al., 2005), although EDS is related to disease duration (Shen et al., 2018), and the occurrence of EDS in idiopathic REM behavior disorder does not predict the conversion to PD (Postuma et al., 2017). The therapies used to treat the motor symptoms contribute to the onset of EDS, but Tholfsen et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acquired results were in accordance with the findings in literature. While it was observed in a study during which ESS and multiple sleep latency test (MSLT) were used for evaluating daytime sleepiness in patients with Parkinson disease that daytime sleepiness is observed in 46.3% of the patients according to ESS which is a subjective test; it was observed that the ratio decreased to 13.4% when MSLT is used which is an objective test (34). We also determined a high ratio of 53.85% in our study for daytime sleepiness according to ESS.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested as a treatment possibility for apathy and fatigue in PD patients (Table 1). 4,[64][65][66][67] Dual Inhibition of Dopamine and Serotonin Uptake UWA-101 [2-(1,3-benzodioxol-5-yl)-1-cyclopropyl-N-methy lethanamine], UWA-121 and S-3,4-methylenedioxy methamphetamine (MDMA) not only constrain DRT, but also the 5-hydroxytryptamine (serotonin, 5-HT) reuptake (SRT). [68][69][70] To date, they were examined only in experimental PD models.…”
Section: Clinical Trialsmentioning
confidence: 99%